2018
DOI: 10.1523/jneurosci.1097-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic mGluRs Control the Duration of Endocannabinoid-Mediated DSI

Abstract: GABA synapses in the brain undergo depolarization-induced suppression of inhibition (DSI) that requires activation of presynaptic cannabinoid type 1 receptors (CB 1 Rs). The brevity of DSI, lasting ϳ1 min in most brain regions, has been ascribed to the transient production of 2-arachidonoylglycerol (2-AG). Here, we propose that the duration of DSI is controlled by heterologous interactions between presynaptic mGluRs and CB 1 Rs. By examining GABA synapses on parvocellular corticotropin-releasing hormone-expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The PVN contains a high density of cells expressing peptide hormones implicated in stress and fear, notably corticotrophin-releasing hormone (CRH) and oxytocin ( Herman and Tasker, 2016 ; Triana-Del Río et al, 2019 ). Though CRH-expressing neurons in the PVN receive input from the BNST ( Colmers and Bains, 2018 ), it is unclear whether oxytocin-producing cells do so. Interesting nonetheless, we found that mouse PVN oxytocinergic neurons strongly innervate the freezing-regulating vl/PAG, replicating earlier work in cats and naked mole rats ( Holstege, 1987 ; Rosen et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…The PVN contains a high density of cells expressing peptide hormones implicated in stress and fear, notably corticotrophin-releasing hormone (CRH) and oxytocin ( Herman and Tasker, 2016 ; Triana-Del Río et al, 2019 ). Though CRH-expressing neurons in the PVN receive input from the BNST ( Colmers and Bains, 2018 ), it is unclear whether oxytocin-producing cells do so. Interesting nonetheless, we found that mouse PVN oxytocinergic neurons strongly innervate the freezing-regulating vl/PAG, replicating earlier work in cats and naked mole rats ( Holstege, 1987 ; Rosen et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate spillover may profoundly affect network excitability by shifting the duration of eCB-mediated inhibition at GABA synapses. Metabotropic glutamate receptors are involved in the control of the duration of DSI, most likely through heterologous desensitization of CB 1 [ 106 ]. Thus, glutamate-mediated excitotoxicity can significantly modify establishment of various forms of synaptic plasticity and balance in glutamate-/GABAergic signaling [ 47 ].…”
Section: The Role Of Retrograde Endocannabinoid Signaling In the Tuning Of Synaptic Strengthmentioning
confidence: 99%
“…The avBST is well-positioned to modulate neuroendocrine responses to stress (25)(26)(27)(28)(29). It provides a GABAergic input to effector neurons in the paraventricular hypothalamic nucleus (PVH) that modulate the hypothalamicpituitary-adrenal (HPA) axis and thereby regulate peripheral glucocorticoid levels in response to a variety of aversive experiences (22,23,(30)(31)(32). Thus, avBST and its projections to the PVH may serve as a critical central regulator of CORT release during the posttraining period of memory consolidation.…”
mentioning
confidence: 99%